Espoused implicit leadership and followership theories and emergent workplace relations: a factorial survey - Hesmert, Laura; Vogel, Rick (Frontiers in Psychology, 2023)
Previous research on implicit leadership and followership theories (ILTs/IFTs) and interpersonal congruence thereof has primarily focused on preexisting, vertical leaderfollower dyads. This study explores interpersonal congruence of ILTs/IFTs at earliest stages of emergent workplace relations in which formal leader and follower roles are not preassigned. We suggest that ILTs/IFTs, when espoused to others, have sorting effects in the social marketplace of organizations toward adaptive workplace relations. We introduce the notion of espoused ILTs/IFTs (i.e., assumptions about leaders and followers that someone claims to have and articulates to others) and examine how congruence of self- and other-espoused ILTs/IFTs facilitates the initiation and emergence of lateral workplace relations in a ‘New Work’ design (i.e., job sharing). Results of an experimental study show that interpersonal congruence in espoused ILTs/IFTs drives attraction to a job sharing partner consistently across different types (ILTs vs. IFTs) and valences (prototypes vs. antiprototypes). While ILTs and IFTs have a similarly strong attraction effect when shared by self and other, the effect of prototype congruence is significantly larger than the effect of antiprototype congruence. The findings encourage leadership scholars to study ILTs/IFTs in a broader range of expression than hitherto and make practitioners aware of similarity biases in the formation of flexible work arrangements.